Civil liability of the person in situation of disability after the reform of the Cuban Civil Code - Pelegrino Toraño, Luis Andrés (2023)
This paper studies the non-contractual civil liability arising from acts performed by persons with disabilities, in accordance with Cuban civil legislation. The study is motivated by the recent reform of the Cuban Civil Code, in September 2022, where the matter related to civil legal capacity was modified, with a view to adapting the Cuban legal system to the postulates of article 12 of the Convention on the Rights of Persons with Disabilities. In such context, where mostly is analyzed matters related to the recognition of the rights of persons with disabilities, the work is focused on the opposite side, that of responsibility. With a view to this, the noncontractual civil liability derived from acts carried out by persons facing situations of disability is studied, both in its variant of liability for their own acts and for the acts of others. The situations in which the direct tortfeasor should be liable are identified, in view of the recognition of his full factual capacity, and therefore full liability, and the cases in which his supports would be liable. It is thus concluded by identifying the positive aspects of the civil liability system in question, as well as those of greater interpretative complexity and deserving of legislative attention in the future comprehensive reform of the Civil Code.